Prioritizing issues of Malaysian vision 2020: an application of the analytic hierarchy process - Islam, Rafikul (2009)
By the year 2020, Malaysia aspires to become a fully developed nation. This lofty vision, known as Vision 2020, was unveiled by the former Prime Minister of Malaysia Tun Dr. Mahathir bin Mohamad in February 28, 1991. By the present time, it is generally felt that the nation has achieved 50 to 60 per cent of the objectives of Vision 2020. “Many more things need to be done by many more people”. What need to be done and in what areas? This is the question we asked to 759 people living in Malaysia (Malaysians as well as Internationals) in a nationwide survey. As expected, the respondents touched upon a wide variety of issues pertaining to education, economy, technology, quality of life, law and order, R&D, and so on. Upon compilation of all the articulated issues, we developed an affinity diagram. The Analytic Hierarchy Process has been applied in each component of the affinity diagram. This exercise identifies the main issues for implementation. The present research findings are expected to provide useful guidelines to the policy makers at the national level in course of fine tuning the Vision 2020 strategies.